1973
DOI: 10.2307/3896574
|View full text |Cite
|
Sign up to set email alerts
|

Use of Molasses Containing Urea as a Supplement to Pangolagrass Pastures in Northeast Mexico

Abstract: Supplements of molasses, molasses + 3% urea, and molasses + 6% urea at a level of approximately 1 kgJhead/day on pangolagrass pasture during the winter and spring months resulted in significantly increased weight for s Zebu x X Criollo bulls. Urea was more effective during the winter months when forage availability was at its lowest, than during the spring months. It is suggested that the use of pangolagrass pasture with molasses and urea supplementation when appropriate could significantly increase production… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1995
1995
1999
1999

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
(2 reference statements)
0
2
0
Order By: Relevance
“…found that yearling heifers responded to supplementation when grazing native range but not improved pastures. Butterworth et al (1973) reported that supplementation was more effective in the winter when forage availability was lowest, than in the spring when more forage was available.…”
Section: Supplementationmentioning
confidence: 99%
See 1 more Smart Citation
“…found that yearling heifers responded to supplementation when grazing native range but not improved pastures. Butterworth et al (1973) reported that supplementation was more effective in the winter when forage availability was lowest, than in the spring when more forage was available.…”
Section: Supplementationmentioning
confidence: 99%
“…It seems probable that purebred Angus cows grazing improved pastures would produce more milk than cows grazing native range. , Butterworth et al (1973), andLandlands and reported that grazing animals responded more to supplementation on lower quality forages. Bowman et al (1995b) concluded that performance and forage intake by supplemented animals were confounded by pasture condition and forage quality.…”
Section: Milk Intakementioning
confidence: 99%